(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Medicinal plants have been the richest drug bio-resource for traditional systems of modern medicines, folk medicines, nutraceuticals, food supplements, pharmaceutical intermediates and chemical entities for synthetic drugs. Among other spices, clove has been widely used for several centuries as medicinal plant due largely to its antimicrobial and antioxidant activities. Various reports confirmed the antifungal, antibacterial, antiviral and anticarcinogenic effects of spice plants. Precisely, clove has attracted a huge attention as a result of the potent antimicrobial and antioxidant effectiveness standing out among other spice plants. In this study, we report the phytochemical screening and antibacterial effectiveness of Syzigium aromaticum, commonly known as clove against clinical isolates of Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. The plant material was extracted using Soxhlet extraction method with ethanol and methanol as the extracting solvents while the antibacterial effectiveness was tested using agar well diffusion method. The phytochemical analyses revealed the presence of various phytochemicals which include flavonoids, glycosides, phenols, saponnins, steroids and tannins. The two extracts were found effective against all the test bacteria with largest and smallest zones of growth inhibition produced against P. aeruginosa and E. coli, respectively at all the concentrations used. In conclusion, different phytochemicals were detected from the ethanolic and methanolic extracts of clove and high effectiveness of the extracts was observed against all the clinical bacterial isolates tested.